2017
DOI: 10.5099/aj170400237
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Correlation between the Expression of Vitamin D receptor (VDR) and Triple Negative Invasive Ductal Carcinoma Tissues

Abstract: Aim: The study was carried out to determine the Immunohistochemical Correlation between the Expression of Vitamin D Receptor (VDR) and Triple Negative Invasive Ductal Carcinoma (IDC) tissues Materials and Method: Twenty two (22) cases of archived female breast Invasive Ductal Carcinoma tissue blocks that are Negative to ER, PR, and HER-2 (Triple Negative) were used. The tissue blocks were sectioned at not more than 2µm each. Haematoxylin and Eosin staining method and immunohistochemical staining technique usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A research reported that water and methanolic extracts of Chrysophyllum albidum leaves used against Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Shigella species suggested that water and methanolic extracts from the leaves may contain active agent(s), which make them susceptible to the tested organisms [20] . Another study reported also that ethanolic extract of Chrysophyllum albidum leaves and stem used against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Salmonella typhi, Klebsiella species, Bacillus subtilis, and Candida albicans were susceptible to plant ethanolic extract [21] [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research reported that water and methanolic extracts of Chrysophyllum albidum leaves used against Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Shigella species suggested that water and methanolic extracts from the leaves may contain active agent(s), which make them susceptible to the tested organisms [20] . Another study reported also that ethanolic extract of Chrysophyllum albidum leaves and stem used against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Salmonella typhi, Klebsiella species, Bacillus subtilis, and Candida albicans were susceptible to plant ethanolic extract [21] [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of Chrysophyllum albidum was shown to reveal the presence of Alkaloids, Cardiac glycoside, Anthraquinones, Flavonoids, Terpenoids, and Steriods, which are useful substances that have medicinal and physiological activities. Vitamin D which is also believe it contain have also been linked with breast cancer [7][8] .…”
Section: Introductionmentioning
confidence: 99%